(untitled) (Medical Forum Monthly, 2024)
Objective: To find the resistance of fluoroquinolones to ESBL producing E. coli causing urinary tract infection. Study Design: Single center observational study. Place and Duration of Study: This study was conducted at the Department of Nephrology, Khyber Teaching Hospital Peshawar from September 2018 to February 2019. Materials and Methods: Urine samples for culture and sensitivity were collected from patients having UTI. Urine cultures for ESBL positive E. coli were included in the study. We analyzed the resistance of fluoroquinolones in ESBL positive E. coli in urinary tract infection. Results: Total of 104 patients were included in the study. Male to female ratio was 1:1.47. Age range was 15 to more than 60 years. Resistance to norfloxacin, ciprofloxacin and levofloxacin was found to be 81.7%, 84.6% and 80.8% respectively. Conclusion: The age group and the gender did not make any statistically significant difference in resistance pattern. There was more than 80% resistance to fluoroquinolones in ESBL positive E. coli urinary tract infection.